Search for CP violation in t(t)over-bar production and decay in proton-proton collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2017)
The results of a first search for CP violation in the production and decay of top quark-antiquark (t (t) over bar) pairs are presented. The search is based on asymmetries in T-odd, triple-product correlation observables, where T is the time-reversal operator. The analysis uses a sample of proton-proton collisions at root s = 8 TeV collected by the CMS experiment, corresponding to an integrated luminosity of 19.7fb(-1). Events are selected having one electron or muon and at least four jets. The T-odd observables are measured using four-momentum vectors associated with t (t) over bar production and decay. The measured asymmetries exhibit no evidence for CP-violating effects, consistent with the expectation from the standard model.
Keywords: CP violation; Hadron-Hadron scattering (experiments); Top physics